Use of Levetiracetam in Epileptic Dogs with Chronic Kidney Disease: A Retrospective Study - So-Yeon Gim (MDPI AG, 2021)
In human medicine, doses of levetiracetam (LEV) are individualized for patients with epilepsy, depending on the status of the patient’s renal function. However, there are not reports on the individualized dosing of LEV for small animals. The aim of this study is to investigate whether a dose adjustment of LEV is needed in dogs with chronic kidney disease (CKD). Patient databases were searched, and 37 dogs with seizures or epilepsy were retrospectively included in this study. Based on pre-existing CKD, patients were divided into a CKD group (n = 20) and a non-CKD group (n = 17). We collected kidney panels before and after LEV treatment. Side-effects were monitored for 1 month after the start of LEV administration. In the CKD group, more dogs developed adverse effects (85%) than in the non-CKD group (52.94%). After LEV administration, an increase in blood urea nitrogen and/or serum creatinine was more often reported in the CKD group than it was in the non-CKD group. Our data indicate that in dogs with seizures or epilepsy with pre-existing CKD, an LEV dose-adjustment is needed. During LEV treatment, CKD patients should be monitored for side-effects and may require laboratory evaluation of renal function.